Obstetric Fistula and Common Peroneal Nerve Palsy in a Rural Based Women: A Case Report - Das, Suchanda; Begum, Rokeya; Chowdhury, Bidhan Roy (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Neglected obstructed labor is a major cause of both maternal and newborn morbidity and mortality. By far the most severe and distressing long term morbidity following obstructed labor is obstetric fistula i.e. Vesicovaginal fistula. In developing countries fistula is commonly the result of prolonged obstructed labor. A18 year old primi gravida was admitted in the labor ward with the involuntary passage of stool and urine and unable to walk after 15 days of her home delivery. Temporary colostomy was done. Patient was on regular physiotherapy for prolonged time and she was responded slowly. There was a plan for repair of Vesicovaginal and Rectovaginal fistula. Obstructed labor complex is completely preventable if high quality basic and comprehensive health services are available to all. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22891 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 71-73